Requirements of Energy and Protein for Arabic Chicken Hens During Late Egg Production Period - Syafwan Syafwan; Yatno Yatno; Ravido Multer Mahulae; Abraham Lincoln; Deby Isabela BR Sembiring (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
The present study aimed to estimate the metabolizable energy (ME) and protein (CP) requirements of Arabic chicken hens during the late egg production period reared under a semi-scavenging system with free-choice feeding. A total of 112 sixty-two-week-old Arabic chicken hens were used. The treatments were control and the choice diet consisted of 6 replicate pens. Control hens received a control diet (2750 kcal of ME/kg and 14.1% of CP) complying with the Hy-line Brown Commercial Management Guide 2011, whereas the choice hens offered control and three other diets (high energy-high protein [3006 and 17.3], high energy-low protein [3089 and 12.7], and low energy-high protein [2656 and 17.0] kcal of ME/kg and % of CP, respectively). Feed, ME, and CP intake, the concentration of dietary ME and CP, and egg production were recorded weekly. Data were analyzed using Proc Mixed of SAS. The feeding method influenced feed intake, CP concentration, and ME concentration but had no significant effect on CP intake, ME intake, and egg production. Weekly feed intake of choice hens was lower than that of control hens (514.03 vs. 551.18 g /hen/week; P<0.03). Dietary concentrations of ME and CP in the choice hens were higher than those in the control hens (2957 vs. 2750 kcal of ME/kg; P<0.001 and 150.6 vs. 14.1 g of CP/kg; P<0.001). Egg production of the choice hens was not significantly higher than that of the control hens (51.17% vs. 46.82%; P>0.05). Feed intake, CP intake, and ME intake decreased significantly at week 66 onward, while egg production decreased at week 65 onward. It can be concluded that Arabic chicken hens in the late egg production period were able to adjust their energy and protein requirements by consuming more from high dietary energy than from a high dietary protein. Based on the choice feeding, ME and CP requirements for Arabic chicken hens during the late egg production period in the semi-scavenging system were 2957 kcal/kg and 151 g/kg and higher than ME and CP contain in the control diet of 2750 kcal/kg and 141 g/kg to maintain egg production. The egg mass and feed conversion ratio were better in the choice hens group.